THE STATE OF THE WHOLE PEOPLE AND THE STRUGGLE FOR SOCIALISM IN THE 21st CENTURY: A PERSPECTIVE OF THE INFLUENCE OF SOCIALISM ON AUSTRALIA - David Matters (World Review of Political Economy, 2010)
The 20th Congress of the Communist Party of the Soviet Union was historically significant for the fundamental revision of Lenin by the introduction of an idealist concept that the proletariat could surrender state power to the whole people and that this voluntary liquidation of the Dictatorship of the Proletariat could happen and still lead to communism. This, coupled with the attack on the cult of the personality, was a cover for an attack on the fundamentals of Leninism and Lenin's view that the class rule represented by this dictatorship will exist right up to communism. This article also shows how this revision influenced the decline in the communist movement in Australia along with the changes caused by the scientific and technical revolution. This led to the reestablishment of a bourgeois state at first without a bourgeoisie major but then seized by the counter-revolutionaries under Yeltsin and Gorbachev.